SPELLBINDERS QUICK & EASY CRAFTS FOR ENTERTAINING - Caron, Stacey; Fox, Tanya (US Annie's Attic, 2012)
Spellbinders Nestabilties, Crafts for Quick & Easy Entertaining is a showcase of stunningly detailed paper craft projects
Contents: Baby shower Garden Party Princess Party Mother's Day Bridal Shower Ladies Night Out New Year's Celebration Holiday Dinner Happy Birthday Celebration Halloween Father's Day Easter Anniversary Party Ice Cream & Cupcake Party Garden Party 2
707033
Paper Craft
Keywords: Entertaining; Paper work